Individual Thigmotactic Preference Affects the Fleeing Behavior of the American Cockroach (Blattodea: Blattidae). Issue 1 (1st February 2018) - Laurent Salazar, Michel-Olivier; Planas-Sitjà, Isaac; Sempo, Grégory; Deneubourg, Jean-Louis
Abstract: Positive thigmotactic behavior is associated with the ability to hide from predators and is important to explain aggregation and collective patterns in various animals. For example, this behavior has been observed in woodlice, domiciliary cockroaches, ants, and fish. Lately, research on different species is focused on the importance of animal personality for ecological and evolutionary processes, individual fitness and group cohesion. In fact, it is generally expected to find some degree of interindividual consistent differences for a behavior, unless specific circumstances, like predator attacks, hide the presence of personalities. In this research, we analyzed the individual thigmotactic preference of domiciliary cockroaches ( Periplaneta americana (Linnaeus, 1758) (Blattodea: Blattidae)) and how it affected the fleeing behavior of isolated individuals inside a shelter after receiving a light stimulus. We notably highlight how isolated individuals show different consistent preferences regarding their position in the shelter, which is due to the individual thigmotaxis level, before the fleeing behavior. During the fleeing itself, cockroaches nearer to the wall, and therefore with more positive thigmotaxis, showed slower reaction lantencies to the stimulus. We propose that thigmotaxis homogenizes the interindividual differences among individuals and is important to explain the individual and collective fleeing behavior.